AFLP and SSR polymorphism in a coffea interspecific backcross progeny [(C. heterocalyx x C. canephora) x C. canephora] - Coulibaly, I; Revol, B; Noirot, M; Poncet, V; Lorieux, Mathias; Carasco-Lacombe, C; Minier, J; Dufour, M; Hamon, P. (Springer, 2003)
An interspecific cross (BC 1) involving a species with one of the largest genomes in the Coffea genus [Coffea heterocalyx (HET), qDNA = 1.74 pg] and a species with a medium-sized genome [Coffea canephora (CAN), qDNA = 1.43 pg] was studied using two types of molecular markers, AFLP and SSR. One hundred and eighty eight AFLP bands and 34 SSR primer pairs were suitable for mapping. The total map length was 1,360 cM with 190 loci distributed in 15 linkage groups. The results were compared to those obtained previously on an interspecific BC 1 progeny involving a species with a medium-sized genome (Coffea liberica var dewevrei, DEW) and a species with one of the smallest genomes (Coffea pseudozanguebariae, PSE). They are discussed relative to three main points: (1) the relevance of the different marker types, (2) the genomic distribution of AFLP and SSR markers, and (3) the relation between AFLP polymorphism and genome size.